MANUFACTURE AND TRADE OF WOOD PRODUCTS IN BULGARIA IN THE IN THE CONTEXT OF STABILITY, GROWTH AND GOVERNMENT POLICY - Neykov, Nikolay; Trichkov, Neno; Todorov, Vladislav; Petkov, Angel (Innovation in Woodworking Industry and Engineering design, 2013)
Over the years before and after the transition of Bulgarian economy from governmentally planned to market economy the wooden products played important role in many regions of the country. During the past few years and especially in the time of crisis many of the enterprises suffered of low revenues and some went bankrupt. It is important to prescreen the past and the present of wood working sector in Bulgaria to reveal its stability and growth.